2001
DOI: 10.1118/1.1408283
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between phantom failure rates and radiation dose in mammography accreditation

Abstract: The American College of Radiology Mammography Accreditation Program (ACR MAP) reviews both clinical mammograms and a phantom image to assess clinical and technical quality from each mammography unit. The phantom contains details representing fibers (speculations), speck groups (microcalcifications), and masses. The depiction of these structures by the mammographic system is scored by medical physicists. The phantom image is taken using the facility's exposure technique for a 4.2‐cm thick breast of average comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…These findings, which characterize aspects of the dose-phantom image quality relationship for a population that is representative of the state of practice, demonstrate that dose has a weak but observable impact on image quality (Figure 12). Haus et al [15] observed a similar relationship in which phantom image score failure rates were significantly higher for doses below 1.0 mGy compared with doses in the range of 1.5-2.0 mGy.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…These findings, which characterize aspects of the dose-phantom image quality relationship for a population that is representative of the state of practice, demonstrate that dose has a weak but observable impact on image quality (Figure 12). Haus et al [15] observed a similar relationship in which phantom image score failure rates were significantly higher for doses below 1.0 mGy compared with doses in the range of 1.5-2.0 mGy.…”
Section: Resultsmentioning
confidence: 78%
“…This finding indicates that film contrast performance should improve because most mammography films currently in use provide optimal image contrast at optical densities approaching 2.0 [14]. Indeed, although there was improvement in all three object groups (Tables 1 and 2), the fibre and mass groups showed the most statistically significant improvement between 1995 and 2006, the visualisations of which are dependent on the contrast performance of the film and therefore sensitive to the background optical density [15]. MQSA requires mammography facilities to maintain a phantom image background optical density of at least 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…The author attributed the poor correlation to the lack of a widespread quality assurance program. On the other hand, a 2001 investigation [14], found a significant correlation between the ACR score and the MGD, and the authors concluded that the correlation reflected the implementation of quality assurance programs and quality control procedures. These interpretations could be applied to the present results.…”
Section: -2mentioning
confidence: 99%
“…Nevertheless, there is good reason to accept that there is a relationship between the above-mentioned variables and both subjective image quality as assessed by a radiologist and diagnostic accuracy ͑sensitivity and specificity͒. [8][9][10][11][12][13] The assessment of image quality in FFDM is further complicated by the image processing applied in FFDM. This can in some instances compensate for limitations or abnormalities in the image acquisition stage; however, it can also introduce artifacts or possibly suppress important image information.…”
Section: B Image Quality and Radiation Dosementioning
confidence: 99%